Monitoring the Effects of Tenofovir Disoproxil Fumarate to Tenofovir Alafenamide Switch for Tubulotoxicity in Highly Treatment-Experienced or in Very Sick Individuals Infected with HIV - Nicole Marie Lioufas; Alan Street; Paul Champion de Crespigny; Stephen G Holt (Journal of Renal and Hepatic Disorders)
Tenofovir disoproxil fumarate (TDF) is a common antiretroviral utilised in the treatment of human immunodeficiency virus (HIV) and hepatitis B infections. It is associated with the development of tubulotoxicity and tubulopathies, and is not recommended in the treatment of patients with baseline chronic kidney disease. Until now, guidelines have suggested frequent monitoring of serum biochemistry to detect the development of such complications. In recent trials, a new prodrug formulation of tenofovir alafenamide (TAF) has been shown to exhibit less tubular toxicity than its counterpart due to a lower serum concentration of its metabolites. In this article, we share our experience with two patients who developed tubulotoxicity following the commencement of TDF-based regimens in HIV, and its improvement following its change to TAF, and review the available literature regarding tenofovir-based nephrotoxicity.